2007
DOI: 10.1103/physreve.76.066704
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically reduced local Navier-Stokes equations for simulation of incompressible viscous flows

Abstract: Recently, another approach to study incompressible fluid flow was suggested [S. Ansumali, I. Karlin, and H. Ottinger, Phys. Rev. Lett. 94, 080602 (2005)]-the kinetically reduced local Navier-Stokes (KRLNS) equations. We consider a simplified two-dimensional KRLNS system and compare it with Chorin's artificial compressibility method. A comparison of the two methods for steady state computation of the flow in a lid-driven cavity at various Reynolds numbers shows that the results from both methods are in good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…These share a theme of locality of data access, yielding better parallel computing efficiency. Similarly, pseudocompressibility methods for fluid flow are potentially better for distributed computing [13,14].…”
mentioning
confidence: 99%
“…These share a theme of locality of data access, yielding better parallel computing efficiency. Similarly, pseudocompressibility methods for fluid flow are potentially better for distributed computing [13,14].…”
mentioning
confidence: 99%
“…The Entropically Damped Artificially Compressible (EDAC) method of Clausen [13,14] is an alternative to the artificial compressibility used by the weakly-compressible formulation. This method is similar to the kinetically reduced local Navier-Stokes method presented in [15,16,17]. However, the EDAC scheme uses the pressure instead of the grand potential as the thermodynamic variable and this simplifies the resulting equations.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the physical phenomena in fluid mechanics are formulated according to the unsteady viscous incompressible Navier-Stokes (INS) equations, which has the nondimensional formula consisting of the momentum equations and the continuity equation [1][2][3][4][5][6][7][8] u + (u ⋅ ∇) u + ∇ = 1 ∇ 2 u,…”
Section: Introductionmentioning
confidence: 99%
“…The KRLNS equations are proposed for the simulation of low Mach number flows in [2], and used the spectral element method to find the numerical solution of the three-dimensional Taylor Green vortex flow. In [3], two-dimensional KRLNS system is simplified and compared with a Chorin's artificial compressibility method for steady state computation of the flow in a lid-driven cavity at various Reynolds numbers, the Taylor Green vortex flow is demonstrated that the KRLNS equations correctly describe the time evolution of the velocity and of the pressure, for this purpose, the explicit Mac Cormack scheme is used. In [5] the KRLNS equations are applied to two-dimensional simulation of doubly periodic shear layers and decaying homogeneous isotropic turbulence, to solve these equations have been used the central difference scheme for the spatial discretization in both advection and diffusion terms and four stages Runge-Kutta method for the time integration, the numerical results are compared with those obtained by the artificial compressibility method, the lattice Boltzmann method, and the pseudospectral method.…”
Section: Introductionmentioning
confidence: 99%